Effects of telephone-delivered lifestyle support on the development of diabetes in participants at high risk of type 2 diabetes: J-DOIT1, a pragmatic cluster randomised trial. Issue 8 (19th August 2015) - Sakane, Naoki; Kotani, Kazuhiko; Takahashi, Kaoru; Sano, Yoshiko; Tsuzaki, Kokoro; Okazaki, Kentaro; Sato, Juichi; Suzuki, Sadao; Morita, Satoshi; Oshima, Yoshitake; Izumi, Kazuo; Kato, Masayuki; et al.
Abstract : Objectives: To examine the effects of telephone-delivered lifestyle coaching on preventing the development of type 2 diabetes mellitus (T2DM) in participants with impaired fasting glucose (IFG). Design: Cluster randomised trial. Setting: 40 groups from 17 healthcare divisions in Japan: companies (31), communities (6) and mixed settings (3). Participants: Participants aged 20–65 years with fasting plasma glucose (FPG) of 5.6–6.9 mmol/L were invited from the 17 healthcare divisions. Randomisation: The groups were then randomly assigned to an intervention or a control arm by independent statisticians according to a computer-generated list. Intervention: The intervention arm received a 1-year telephone-delivered intervention provided by three private lifestyle support centres (at different frequencies: low-frequency (3 times), middle-frequency (6 times) and high-frequency (10 times) support calls). The intervention and control arms both received self-help devices such as a weight scale and pedometer. Outcomes: Participants were followed up using data from annual health check-ups and a questionnaire regarding lifestyle. The primary outcome was the development of T2DM defined as FPG ≥7.0 mmol/L, the diagnosis of diabetes, or use of an antidiabetic drug, confirmed by referring to medical cards. Results: Of 14 473 screened individuals, participants were enrolled in either the intervention (n=1240) arm or control (n=1367) arm. Overall, the HR for the development of T2DM in the intervention arm during 5.5 years was 1.00 (95% CI 0.74 to 1.34). In the subanalysis, the HR was 0.59 (95% CI 0.42 to 0.83) in the subgroup that received phone calls the most frequently, compared with the control arm. A limitation of the study includes a lack of blinding. Conclusions: High-frequency telephone-delivered lifestyle support could effectively prevent T2DM in participants with IFG in a primary healthcare setting, although low-frequency and middle-frequency phone calls did not. Trial registration number: This trial has been registered with the University Hospital Medical Information Network (UMIN000000662).